The learning continuum of living reproduction: Generating a curriculum grid based on students' cognitive levels - Desi Trilipi; Bambang Subali (University of Muhammadiyah Malang, 2020)
One of the overlapping curriculum designs indicates the mismatch of teaching materials with the cognitive level process and student development, impacting the unstructured qualification of mastery of the material. On the other hand, the breadth and depth of teaching materials in the curriculum must be following students' mental development and level of cognitive processes. This study aims to collect the opinions of science teachers in junior high schools and biology teachers in high schools about the learning continuum design on reproducing living things. The method used is a survey. The study population is a hypothetical population with a convenience sample. The sample involved in this study were 111 teachers in Bantul Regency and Yogyakarta City. The data collection method used a questionnaire distributed through four subject teachers' conference (MGMP). The data obtained were analyzed using descriptive analysis. The results showed several sub-aspects of reproduction of living things that cannot be taught in elementary schools. The material for propagating fungi, protists, bacteria, and viruses starts in grade VII with a cognitive level of C1 (remembering), after previously students received material about types of animals and plants in grade VI (elementary school). Furthermore, the material on reproductive anatomy and physiology can only be given to class IX with cognitive level C2 (understanding) and continued in class X and XI with cognitive level C4 (analyzing). Especially for reproductive anatomy and physiology, fungi were introduced to class VII with C1 level cognitive processes (remembering). This teacher opinion generates a learning continuum grid that can help policymakers improve educational curriculum.